Enhancing Sensitivity to Conflict Risks in World Bank-funded Activities : Lessons from the Kyrgyz Republic - World Bank Group (Bishkek, 2014)
The Kyrgyz Republic is a landlocked mountainous country of 5.5 million and home to several ethnic groups. Nevertheless, economic stagnation, rising corruption, and inter-ethnic tensions have posed risks to the country's stability. Following the revolution and ethnic disturbances in 2010, the World Bank introduced a conflict filter for its Kyrgyz Republic operations in 2011 as a screening tool to ensure that Bank projects do not exacerbate conflict risks. The objectives of the conflict filter were: (i) assisting task teams to be cognizant of the context in which they operate in the Kyrgyz Republic; (ii) assisting task teams in identifying and managing the conflict and fragility risks in the World Bank-supported activities; (iii) supporting task teams and the client in identifying measures to help strengthen trust, social inclusion, and social cohesion in the context of World Bank supported activities and in targeted project areas; and (iv) assisting task teams and the clients in applying good practices for conflict management and citizen engagement in fragile environments. The application of the conflict filter has evolved over time in three distinct stages: in the first stage, a country-wide conflict analysis was undertaken and a matrix was developed. In the second stage, the conflict filter team applied the conflict filter matrix in a comprehensive manner, covering all projects in the portfolio. In the third stage (July 2014-June 2014), the conflict filter adopted a more selective and practical approach by focusing primarily on projects under preparation. This note summarizes the application of the conflict filter to the Bank's Kyrgyz Republic portfolio during its third year of implementation. The note provides a brief update on recent conflict and fragility dynamics in the country. It also provides a summary of the activities with a focus on selected projects where the application of the conflict filter influenced project design and implementation. Finally, the note shares some lessons learned to guide future conflict filter application in the Kyrgyz Republic and elsewhere.